Nilai Hidup dalam Keringat: Penelitian terhadap Para Pemulung di Sekitar Alun-alun Kota Malang - Eric Hariyanto, Benedictus; Iswandir, Lorentius; Badri Dinggit, Patrisius Juwantri (Sekolah Tinggi Widya Sasana, 2024)
The purpose of this paper is to explore the meaning of daily life lived by scavengers within the framework of the philosophical ethics of Aku and Liyan according to Armada Riyanto's perspective. This goal is achieved through describing the daily life of waste pickers in Malang city square and finding the meaning of life from the perspective of the daily life of the waste pickers. The process of finding the meaning of life is based on the concept of relational love of Aku and Liyan according to Armada Riyanto. This type of qualitative research uses phenomenological research methodology with observation and interview techniques. The findings of this research are based on the results of the research and the process of philosophical reflection, it can be concluded that life according to scavengers is a love activity between Aku (scavenger) and Liyan (scavenger family members) in daily life. The love activity is carried out continuously. The peak of the love relationship occurs when I give love to Others, even though it does not bring comfort to Me.